”Fore wor (...) siæle bestands og salighetz skild”: Om kongelige stiftelser og sjælegaver fra kong Hans’ og dronning Christines tid - Johannsen, Birgitte Bøggild (Kirkehistoriske Samlinger, 1999)
The starting point of this article is the rich ornamentation of the chancel of the now demolished Grey Friars’ Church of Odense, made in the Late Middle Ages and probably established on the initiative of Queen Christine in connection with the arrangement of the chancel as a mausoleum for King Hans, for herself, and for their nearest relations. Furthermore the article gives an outline of foundations and frankalmoins donated by the royal couple and their immediate predecessors and successors on the throne. An account is given of both liturgical foundations and donations of material benefits to churches and religious houses, being contributions to buildings and equipment. The source material is commented upon - with special emphasis on the lack of royal wills from the period - and a description is made of royal foundations and donations to cathedrals, to town churches, to village churches, as well as to the religious houses. In conclusion a comment is given on the extent of the liturgical foundations which was, as compared with what was usual at other European courts, comparatively modest. The general character of the foundations is discussed, in so far as the preserved sources allow this, and as a special aspect of the royal foundations, which is especially notable in the ornamentation of the sepulchral chancel of the Grey Friars’ Church of Odense, the intended selfassertion and glorification of the dynasty is seen as evidence of the incipient cultural watershed of the dawn of the Renaissance.